This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
yoneda_embedding [2015/03/14 01:10]
yoneda_embedding [2015/03/14 01:13] (current)
Line 29: Line 29:
 $h\circ g : \mathrm{Hom}(X,​A)$ ... $f\circ h\circ g : \mathrm{Hom}(X,​B)$ ​ $h\circ g : \mathrm{Hom}(X,​A)$ ... $f\circ h\circ g : \mathrm{Hom}(X,​B)$ ​
 +Note how the $\mathrm{Hom}$-functors themselves are contravariant,​ as seen by the direction of the vertical arrows: $g: X\to Y$ but e.g. the associated fmap goes from $\mathrm{Hom}(Y,​A)$ to $\mathrm{Hom}(X,​A)$.
 === Yoneda lemma === === Yoneda lemma ===
Link to graph
Log In
Improvements of the human condition